Budidaya Ikan Lele dengan Sistem Bioflok untuk Kawasan Permukiman - Candra Dwiratna Wulandari; Sudiro Sudiro; Titik Poerwati (University of Merdeka Malang, 2020)
Households themselves should fulfill their nutritional needs by using the home page. Limited land in residential areas is one of the constraints that limit this. One of the Rukun Tengga (RT) in Tlogomas Village, namely RT 05 RW 03 is a new RT, which does not yet have complete infrastructure, to catch up every year it is planned and budgeted to develop these facilities and infrastructure. One of them is in the field of food security, RT 05 tries to meet the needs of vegetables, fruit and fish in the surrounding environment, so catfish farming is developed using conventional methods. The problem faced by the manager is that catfish cultivation is not optimal so that the mortality of catfish seeds reaches 50 percent, and another obstacle is the presence of an unpleasant odor. To solve this problem, the biofloc method was carried out to improve the catfish culture system. From the efforts to improve catfish culture by means of biofloc, there are benefits, among others, the percentage of seed mortality has decreased to 20 percent, the cost of feed is more efficient, does not cause odor and the development of catfish is maximized. The yields are in accordance with market demand, namely, with a weight of 1 kg as many as 8 fish at the age of 2.5 months.DOI: https://doi.org/10.26905/abdimas.v5i3.4044